Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Hasil Belajar Siswa - Muhammad Restu Adji; Muhammad Arif Prasetyo; Lisa Katun Nada; Lisa Ulandari; Laila Fadila (Griya Journal of Mathematics Education and Application, 2023)
Research that is directly related to the effect of the jigsaw cooperative learning model on improving student learning outcomes has been widely carried out. These studies still need to be identified, reviewed, and generalized concluded so that they can be studied better. This study aims to analyze and examine research by identifying and classifying all research results related to the influence of the jigsaw cooperative model on improving mathematics learning outcomes in Indonesia in 2015-2022. This study uses the Systematic Literature Review (SLR) method. There are 20 related articles analyzed in this study. The results of this SLR indicate that there is research on the application of the jigsaw cooperative learning model to improve mathematics learning outcomes. Most article publications occurred in 2020 and most were implemented at the SMP/MTs level. Research using quantitative methods is the dominating method and flat shape material is the material most taught to students. In general, based on the research results, it shows that the jigsaw cooperative learning model has a very positive impact on improving mathematics learning outcomes. The results of this study can be a consideration for researchers in conducting research and for teachers in implementing classroom learning.